Optimalisasi SDM Melalui Pembentukan Pokdarwis Serta Pelatihan Pengolahan Jeruk di Desa Bonyoh - I Nyoman Abdi; Putu Adi Suprapto; Ni Luh Ayu Kartika Yuniastari Sarja; Ni Ketut Pradani Gayatri Sarja; Kadek Adi Parthama (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
Bonyoh Village trying to be touritm village with natural potential of orange plantations. The potential is not accompanied by human resources, this is due to lack of tourism awareness and knowledge regarding management of tourism potential. Problems faced by Bonyoh Village are the absence of a driving agency to increase the role of the community in tourism potential, lack knowledge of processing orange into selling value products and their marketing. Based on these problems, service activities implemented in the formation of Pokdarwis by including training on the development of citrus plantation businesses and their marketing as well as training on tourism villages, ticketing, guiding and promoting. The method used is discussion, mentoring and training and development. Evaluation show that 100% of Pokdarwis formation realized, 2 people can process them into products, 1 person can do marketing on social media and 50% of participants' knowledge increases regarding tourist villages, ticketing, guiding and promoting towards a new Tourism Village in Bangli Regency.